1997
DOI: 10.2527/1997.7592561x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat middlings in high-concentrate diets: feedlot performance, carcass characteristics, nutrient digestibilities, passage rates, and ruminal metabolism in finishing steers.

Abstract: We conducted two experiments to determine the feeding value and effects on diet digestibilities, passage rates, and ruminal metabolism of wheat middlings (WM) fed as a replacement for either the concentrate or roughage components of finishing diets of steers. In Exp. 1, 120 medium-framed steers were blocked by weight and randomly allocated to one of six treatments of high-concentrate diets: control (0%); 5, 10, or 15% pelleted WM replacing dry-rolled corn (DRC); and 5 or 10% pelleted WM replacing chopped alfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
5
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
0
11
5
2
Order By: Relevance
“…Brandt et al (1986) observed linear reductions in daily gain and feed efficiency for finishing steers when WM was substituted for corn in a 120 -d study using pelleted WM. Dalke et al (1997) reported no differences (P > 0.05) between treatments for hot carcass weight, backfat depth, quality grade, and dressing percentage, although marbling score was increased linearly with increasing WM in the diet. Our study showed similar results, with the exception of marbling score.…”
Section: Finishing Steersmentioning
confidence: 89%
See 2 more Smart Citations
“…Brandt et al (1986) observed linear reductions in daily gain and feed efficiency for finishing steers when WM was substituted for corn in a 120 -d study using pelleted WM. Dalke et al (1997) reported no differences (P > 0.05) between treatments for hot carcass weight, backfat depth, quality grade, and dressing percentage, although marbling score was increased linearly with increasing WM in the diet. Our study showed similar results, with the exception of marbling score.…”
Section: Finishing Steersmentioning
confidence: 89%
“…Blasi et al (1998), however, as previously stated, showed that ADG and FE decreased linearly as WM level increased in limit-fed diets. Dalke et al (1997) conducted an experiment to determine the feeding value and effect on finishing steer feedlot performance when WM replaced dry-rolled corn or chopped alfalfa hay. They concluded that WM could replace only 5% of the dry-rolled corn in the finishing diets without reducing feedlot performance.…”
Section: Finishing Steersmentioning
confidence: 99%
See 1 more Smart Citation
“…Soares et al (2004), em pesquisa com níveis crescentes de farelo grosso de trigo (0, 33, 67 e 100%) em substituição ao fubá de milho para vacas leiteiras, também verificaram redução nos coeficientes de digestibilidade da matéria seca das dietas. Dalke et al (1997) avaliaram a substituição do farelo de trigo (5, 10 e 15%) por subproduto do milho e verificaram decréscimo linear nos coeficientes de digestibilidade da matéria seca e da matéria orgânica com o aumento dos níveis de farelo de trigo na dieta. Ao contrário, Dhakad et al (2002) avaliaram a substituição do fubá de milho por farelo de trigo em dietas para ovinos e não encontraram variações nos coeficientes de digestibilidade da matéria seca, matéria orgânica e dos carboidratos totais.…”
Section: Resultsunclassified
“…Estes resultados estão de acordo com Dalke et al (1997), que observaram decréscimo linear da digestibilidade da MS e MO quando o farelo de trigo substituiu o fubá de milho; entretanto, quando este substituiu o feno de alfafa, as digestibilidades aumentaram linearmente. Dhakad et al (2002), quando avaliaram a substituição do milho triturado (0, 50 e 100% da MS) por farelo de trigo na ração concentrada de ovinos em crescimento, constataram que as digestibilidades de MS, MO, PB, FDN, FDA e EE não variaram, indicando que a substituição do milho pelo farelo de trigo em níveis tão elevados quanto 100% não alterou a digestibilidade dos nutrientes.…”
Section: Table 5 -Average Daily Intakes Of Dry Matter (Dm) Organic Munclassified